Serum retinyl esters are positively correlated with analyzed total liver vitamin A reserves collected from US adults at time of death - Olsen, Kiersten; Suri, Devika J; Davis, Christopher; Sheftel, Jesse; Nishimoto, Kohei; Yamaoka, Yusuke; Toya, Yutaka; Welham, Nathan V; Tanumihardjo, Sherry A (The American journal of clinical nutrition, 2018)
Minimal human data exist on liver vitamin A (VA) compared with serum biomarkers. Cutoffs of 5% and 10% total serum VA as retinyl esters (REs) suggest a VA intoxication diagnosis. We compared total liver VA reserves (TLRs) with the percentage of total serum VA as REsto evaluate hypervitaminosis with the use of US adult autopsy samples.Secondary objectives evaluated serum retinol sensitivity, TLRs among lobes, and hepatic α-retinol concentrations, an α-carotene cleavage product. Matched serum and liver samples were procured from cadavers (n = 27; mean ± SD age:70.7 ± 14.9 y; range: 49–101 y). TLRs and α-REs were quantified byultra-performance liquid chromatography. Pearson correlations showedliver and serum associations. Sensitivity and specificity werecalculated for >5%, 7.5%, and 10% total serum VA as REs to predictTLRs and for serum retinol <0.7 and 1 μmol/L to predictdeficiency Serum RE concentrations were correlated with TLRs (r = 0.497,P < 0.001). Nine subjects (33%) had hypervitaminosis A (≥1.0 μmol VA/g liver), 2 of whom had >7.5%total serum VA as REs; histologic indicators corroborated toxicity at3 μmol/g liver. No subject had >10% total serum VA as REs. Serum retinol sensitivity to determine deficiency (TLRs <0.1 μmol VA/g)was 83% at 0.7 and 1 μmol/L. Hepatic α-retinol was positively correlated with age (P = 0.047), but removing an outlier nullified significance. This study evaluated serum REs as a biomarker of VA statusagainst TLRs (gold standard), and abnormal histology suggested that7.5% total serum VA as REs is diagnostic for toxicity at theindividual level in alts. The long-term impact of VA supplements and fortificants on VA status is currently unknown. Considering the high prevalence of hypervitaminotic TLRs in this cohort, and given that many countries are adding preformed VA to processed products, population biomarkers diagnosing hypervitaminosis before toxicity are urgently needed. This trial was registered atclinicaltrials.govas NCT03305042.